Kunci Keberhasilan Agen Perubahan Menurut Tenaga Administrasi Sekolah Di MAN 1 Kota Bukittinggi, Kota Bukittinggi - Linda Juliana (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to examine the keys to the success of change agents based on the perspectives of administrative staff at MAN 1 Kota Bukittinggi. Change agents can be understood as individuals or groups capable of influencing, directing, and implementing organizational innovations to improve quality. This study employs a qualitative approach with a descriptive method through observation, interviews, and documentation. The research subjects focus on the administrative staff and teachers at MAN 1 Kota Bukittinggi. The results indicate that the success of change agents at MAN 1 Kota Bukittinggi is determined by four main factors: the efforts of change agents in establishing effective communication, alignment of change objectives with the vision and mission of the madrasa, the relevance of innovations to the needs of teachers and students, and the high empathy of the principal and educators towards organizational dynamics. Moreover, the implementation of ISO as a quality standard, the credit system program (SKS), quality improvement workshops, and the use of digital technologies such as AI Talent DNA in counseling services represent tangible manifestations of directed change. The findings of this study provide theoretical contributions in strengthening the concept of change agents in the context of Islamic education, as well as practical recommendations for schools to continuously foster a culture of innovation and participatory leadership.